The insurrectionary captaincy: the declaration of war against the Southern Gê by D. João VI’s Court and the preparation of the Royal Expedition of Conquest of their territories in the Koran-bang-rê – Campos de Guarapuava (1774 -1810) - Mota, Lucio Tadeu [UNESP] (My University, 2023)
This reflection aims to demonstrate that the Indigenous groups who lived in the tplanning and organization to invade and occupy the Kaingang territorieerritories in the stretch that goes from the south of the Captaincy of São Paulo to the Captaincy of São Pedro do Rio Grande do Sul, were insurgent and defended their territories against invaders. The Xokleng were found in the territories adjacent to Viamão road, from Campos de Lages to the vicinity of Vila do Príncipe, currently the city of Lapa PR, while the Kaingang occupied the east causing insecurity among cattle drivers, and endangering farms and villages in Campos Gerais do Paraná and Campos de Itapetininga reaching Sorocaba in São Paulo. It also seeks to elucidate that the Royal Charter of 11/05/1808 was the D. João VI’s court reaction to this state of war on the borders of the occupation, while the Royal Charter of 04/01/1809 was a meticulously traced plan for the Royal Expedition of Conquest of Guarapuava to occupy the Kaingang territories in the Campos de Guarapuava.
A capitania insurrecta: a declaração de guerra contra os Jê do Sul pela Corte Joanina e a preparação da Real Expedição para a conquista dos seus territórios nos Koran-bang-rê – Campos de Guarapuava (1774 -1810)
Keywords: Conquest of Guarapuava; Indigenous Ethnohistory; Kaingang Indigenous Peoples; Royal Charters; Sociocultural relations